EXPLORING THE EXPENDITURES OF FOREIGN TOURISTS IN TAIWAN ON LOCAL SPECIALTY PRODUCTS AND TEA - Yu, Teng-Li; Wang, Jiun-Hao; Wang, Szu Yung (PEOPLE: International Journal of Social Sciences, 2018)
In order to understand the expenditures of tourists in Taiwan regarding tea and local famous specialty products, it is essential to examine the demographic nature of the inbound tourists. In this study, information was gathered from the 2015 Annual Survey Report on Visitors’ Expenditures and Trends in Taiwan of the Tourism Bureau, Ministry of Transportation and Communications (MOTC), which included 6277 respondents, and analyzed by using ordinary least squares (OLS) regression methods. The analysis shows that gender, age, education, income, country of origin, travel purpose, travel type, and number of days stayed in Taiwan were the most significant factors to forecast the level of purchasing of tea and specialty products. With a greater understanding of these factors, the tourism industry in Taiwan will be able to increase revenue and improve their products and services. Meanwhile, as a reference for Taiwanese government can re-examine its tourism market to establish new policies and marketing plans to boost local economy.